Penerapan Media Pembelajaran Papan Pintar Muatan IPA Perubahan Wujud Benda Di Sekolah Dasar - Isnaini Wahyuningrum; Septi Adelia Putri; Nela Rofisian (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The science learning process in elementary schools needs to involve students taking an active and enthusiastic role. This is facilitated by using the application of smart board learning media which can attract students' attention to be active and enthusiastic. This research is research that refers to a qualitative approach method. In this research the researcher used the observation and interview method, because with the observation method the researcher will get valid data. At SD Negeri 1 Glagahwangi the researcher saw that the learning media used by class III educators was less attractive to students so that it could influence the student learning outcomes process. . Seeing this problem, researchers will develop the application of smart board learning media that attracts students' attention so that it can make it easier for students to understand the explanations given by educators. The application of media in teaching and learning activities, especially at the elementary school level, is very important. Learning media can also attract students' attention, increase enthusiasm for learning and train students' thinking power.